2013
DOI: 10.3389/fnhum.2013.00054
|View full text |Cite
|
Sign up to set email alerts
|

Trait anxiety modulates fronto-limbic processing of emotional interference in borderline personality disorder

Abstract: Previous studies of cognitive alterations in borderline personality disorder (BPD) have yielded conflicting results. Given that a core feature of BPD is affective instability, which is characterized by emotional hyperreactivity and deficits in emotion regulation, it seems conceivable that short-lasting emotional distress might exert temporary detrimental effects on cognitive performance. Here we used functional magnetic resonance imaging (fMRI) to investigate how task-irrelevant emotional stimuli (fearful face… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
34
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 120 publications
(183 reference statements)
5
34
0
1
Order By: Relevance
“…The observed left amygdala-anterior cingulate hyperconnectivity is also in agreement with the role assigned by theoretical and animal studies to frontolimbic connections as modulators of cognitive-emotional control of behavior (13,14) and could also be the cause of the interferences reported in functional MRI studies combining emotional and cognitive or inhibition tasks (66)(67)(68). Overall, our results support the theoretical model in which the amygdala, associated with emotional processing, is modulated by frontomedial structures controlling the complex manifestations and behavior derived from these same emotions.…”
Section: Discussionsupporting
confidence: 87%
“…The observed left amygdala-anterior cingulate hyperconnectivity is also in agreement with the role assigned by theoretical and animal studies to frontolimbic connections as modulators of cognitive-emotional control of behavior (13,14) and could also be the cause of the interferences reported in functional MRI studies combining emotional and cognitive or inhibition tasks (66)(67)(68). Overall, our results support the theoretical model in which the amygdala, associated with emotional processing, is modulated by frontomedial structures controlling the complex manifestations and behavior derived from these same emotions.…”
Section: Discussionsupporting
confidence: 87%
“…Patients’ counter-intuitively increased and decreased intra-iFC in intrinsic networks particularly in one and the same network (such as lCEN) has been observed also in other neuropsychiatric disorders such as schizophrenia (Manoliu et al, 2013b) or Alzheimer’s disease (Zhou et al, 2010) and – in line with our findings – in BPD (for the DMN and CEN; Wolf et al, 2011); however, the functional significance of the direction of intra-iFC changes in brain disorders is still unclear (e.g., iFC decreases are suggested to reflect connectivity disruptions while iFC-increases might reflect compensatory processes; but also a loss of desynchronization and therefore system complexity may play a role; Zhou et al, 2010). Previous imaging studies, which explored the neural correlates of impaired self- or emotion-processing in BPD, revealed aberrant task-related activity in areas similar to those of aberrant intra-iFC we found (Minzenberg et al, 2007; King-Casas et al, 2008; Driessen et al, 2009; Koenigsberg et al, 2009a; Smoski et al, 2011; Holtmann et al, 2013). For example, patients with BPD, who had to engage with emotional stimuli, had aberrant levels of activity in ACC, dorsolateral PFC, and amygdala (Minzenberg et al, 2007; Koenigsberg et al, 2009a; Holtmann et al, 2013); the insula was found to be the key region distinguishing BPD patients from HC in a more complex setting of a gambling task (King-Casas et al, 2008); in healthy subjects, self-distancing of negative pictures activates parietal regions overlapping with DMN (Koenigsberg et al, 2009b), while patients with BPD fail to activate the DMN.…”
Section: Discussionsupporting
confidence: 72%
“…Previous imaging studies, which explored the neural correlates of impaired self- or emotion-processing in BPD, revealed aberrant task-related activity in areas similar to those of aberrant intra-iFC we found (Minzenberg et al, 2007; King-Casas et al, 2008; Driessen et al, 2009; Koenigsberg et al, 2009a; Smoski et al, 2011; Holtmann et al, 2013). For example, patients with BPD, who had to engage with emotional stimuli, had aberrant levels of activity in ACC, dorsolateral PFC, and amygdala (Minzenberg et al, 2007; Koenigsberg et al, 2009a; Holtmann et al, 2013); the insula was found to be the key region distinguishing BPD patients from HC in a more complex setting of a gambling task (King-Casas et al, 2008); in healthy subjects, self-distancing of negative pictures activates parietal regions overlapping with DMN (Koenigsberg et al, 2009b), while patients with BPD fail to activate the DMN. Furthermore, so far limited literature of resting-state imaging data in BPD supports the spatially widespread pattern of functional changes in BPD.…”
Section: Discussionsupporting
confidence: 72%
“…Neural structures implicated in ER include frontal brain regions including the OFC, the ventrolateral PFC (vlPFC), and the dorsolateral PFC (dlPFC), depending on the emotion being regulated (for reviews see Gross and Thompson, 2007; Beauchaine, 2015b; Beauchaine et al, 2017). These frontal regions provide top-down inhibition of subcortical, limbic circuits that generate emotion, including the amygdala, hippocampus, insula, fusiform gyrus, and striatum, among others (Brendel et al, 2005; Kalisch, 2009; Dell'Osso et al, 2010; Holtmann et al, 2013; Sitaram et al, 2014). In fact, the amygdala (Kalisch, 2009; McRae et al, 2010), hippocampus (Phelps, 2003; Sripada et al, 2013), fusiform gyrus (Pollatos and Gramann, 2012; Fonville et al, 2014), striatum (Koelsch, 2014), and thalamus (Cheung et al, 2006) are all implicated in emotional reactivity, whereas the OFC (Ito, 2004; Rempel-Clower, 2007), vlPFC, dlPFC (Elliott, 2003; Chan et al, 2008; Levy and Wagner, 2011), and anterior insula (Sitaram et al, 2014) are implicated in effortful regulation of emotion (see Schulze et al, 2011).…”
Section: Emotion Regulationmentioning
confidence: 99%